Performance of hydroponics of peas with barley and wheat in the production of germinates - Contreras H., José Luis (2015)
The aim of this study was to determine the effects of the associations pea-barley and pea-wheat in six ratios (0/100, 20/80, 40/60, 60/40, 80/20, 100/0) of hydroponics on the percentage of dry matter, organic matter and crude protein, height of the plant, and on the yield of green fodder, dry matter, organic matter and crude protein. A randomized factorial 2 x 6 (ratio x association) with 5 replicates per treatment was used. The percentage of dry matter and yield of green fodder were statistically similar in pea-barley and pea-wheat associations. The percentages of organic matter and crude protein were affected by the association and the level of legume/grass ratio. The average percentage of crude protein in both associations was 22.37%. The proportion of legume/grass did not affect plant height.